(3JaSjQ GdbQBf GdcQjes - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3fMeO Gddg Ld PcQg HLejY eMGeOg hfKfi Ydjg HJhGJQ CdGFg hfYeg s
(3BNQgG (B:s
(3jfJgi HJaSjQ bhdg JYGdi (B" (3VQHJ Ydjge GdPdg CjfeG KbahG GdG HMd ef Gddg GdCjI eYfGgG GdRe Gddg GdecPHjf deMeO GdPdI CdG HMHd ef Gddg Ci HSHH ef Gddg s
(3HgG CKGQ JbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs